2006
DOI: 10.1158/1078-0432.ccr-05-2603
|View full text |Cite
|
Sign up to set email alerts
|

Phase II Trial of Bevacizumab in Combination with Weekly Docetaxel in Metastatic Breast Cancer Patients

Abstract: Purpose: To evaluate the safety and efficacy of bevacizumab and weekly docetaxel as first-or second-line therapy in patients with metastatic breast cancer (MBC). Patients and Methods: Twenty-seven MBC patients received i.v. bevacizumab at 10 mg/kg on days 1and 15 in combination with i.v. docetaxel 35 mg/m 2 on days 1, 8, and 15 of a 28-day cycle. Primary end points were to assess toxicity, overall response rate, and progression-free survival. A secondary end point was to assess the relationship between plasma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
58
1
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(64 citation statements)
references
References 28 publications
(19 reference statements)
3
58
1
2
Order By: Relevance
“…SDF-1 was suggested by previous studies as a target for renal carcinoma therapy (Reckamp et al, 2008), and increased levels of this cytokine have been shown in sunitinib-treated mice (Ebos et al, 2007). ICAM-1 levels were also checked for validation, because plasma levels of this cytokine have been associated with a response to the anti-VEGF targeting agent bevacizumab in combination with docetaxel in metastatic breast cancer (Ramaswamy et al, 2006). Vascular endothelial growth factor (VEGF) was quantified as well, because its receptors are primary targets of sunitinib.…”
Section: Resultsmentioning
confidence: 99%
“…SDF-1 was suggested by previous studies as a target for renal carcinoma therapy (Reckamp et al, 2008), and increased levels of this cytokine have been shown in sunitinib-treated mice (Ebos et al, 2007). ICAM-1 levels were also checked for validation, because plasma levels of this cytokine have been associated with a response to the anti-VEGF targeting agent bevacizumab in combination with docetaxel in metastatic breast cancer (Ramaswamy et al, 2006). Vascular endothelial growth factor (VEGF) was quantified as well, because its receptors are primary targets of sunitinib.…”
Section: Resultsmentioning
confidence: 99%
“…Avastin ® (Genentech) is a VEGF-neutralizing antibody that, when used in combination with chemotherapy, prolongs the progression-free survival of breast cancer patients [19,20], presumably due to its ability to suppress tumor angiogenesis [21]. Based on this activity, Avastin ® was recently approved as a therapy for patients with HER2-negative metastatic breast tumors.…”
Section: Resultsmentioning
confidence: 99%
“…In MBC, a single-arm, phase II study of bevacizumab in combination with docetaxel and trastuzumab showed a PFS interval of 7.5 months (95% confidence interval [CI], 6.2-8.3 months) [22]. In other preliminary reports, the combination of bevacizumab (10 mg/kg every 2 weeks) with trastuzumab in human epidermal growth factor receptor 2-positive MBC patients appeared to be well tolerated, with few grade 3 or 4 side effects [23].…”
Section: Other Investigational Combination Therapiesmentioning
confidence: 99%